Fracture-initiation pressure model of inclined wells in transversely isotropic formation with anisotropic tensile strength. (November 2022) - Ma, Tianshou; Wang, Haonan; Liu, Yang; Shi, Yufan; Ranjith, P.G.
Abstract: Fracture-initiation pressure (FIP) is closely related to lost circulation and hydraulic fracturing. However, conventional prediction models often treat formation rock as an isotropic medium, ignoring the anisotropy of rock materials, particularly, the anisotropy of tensile strength. Therefore, a universal FIP model was proposed for inclined well in transversely isotropic formations, and the combined effects of both anisotropic elasticity and tensile strength were taken into account. The proposed model was verified by indoor experiments, and the predicted FIPs of isotropic and anisotropic models were compared. Finally, the influencing factors of FIP were investigated. The results indicated that compared with the experimental results, the present model is more consistent than traditional models, and the deviation factor is concentrated between 0.8 and 1.4. Compared with the traditional isotropic model, the maximum differences of the elastic anisotropic model, strength anisotropic model, and the present model are 0.059 g/cm 3, 0.262 g/cm 3, 0.258 g/cm 3, respectively. The dip direction has almost no effect on the FIP at a low dip angle, while it has a significant effect at a high dip angle. The FIP is the minimum when the dip direction is parallel to the azimuth of wellbore, while it is the maximum when the dip direction is perpendicular to the azimuth of wellbore. With the increase of anisotropy index, the influence of elastic anisotropy and strength anisotropy is enhanced, and the maximum difference is 0.31 g/cm 3 and 0.33 g/cm 3 respectively; while the Poisson's ratio only has a small effect, and the maximum difference is only 0.256 g/cm 3 . The spatial distribution parameter ( Ω 0 ) directly affects the variation trend of tensile strength, too high a Ω 0 may overestimate the FIP, while too low a Ω 0 may underestimate the FIP. The present model and analysis results can provide theoretical guidance for lost circulation prevention and hydraulic fracturing optimization.